Preparation and optimisation of anionic liposomes for delivery of small peptides and cDNA to human corneal epithelial cells. (18th May 2016) - Neves, Luís F.; Duan, Jinghua; Voelker, Adrienne; Khanal, Anil; McNally, Lacey; Steinbach-Rankins, Jill; Ceresa, Brian P.
Abstract: Drug delivery to corneal epithelial cells is challenging due to the intrinsic mechanisms that protect the eye. Here, we report a novel liposomal formulation to encapsulate and deliver a short sequence peptide into human corneal epithelial cells (hTCEpi). Using a mixture of Phosphatidylcholine/Caproylamine/Dioleoylphosphatidylethanolamine (PC/CAP/DOPE), we encapsulated a fluorescent peptide, resulting in anionic liposomes with an average size of 138.8 ± 34 nm and a charge of −18.2 ± 1.3 mV. After 2 h incubation with the peptide-encapsulated liposomes, 66% of corneal epithelial (hTCEpi) cells internalised the FITC-labelled peptide, demonstrating the ability of this formulation to effectively deliver peptide to hTCEpi cells. Additionally, lipoplexes (liposomes complexed with plasmid DNA) were also able to transfect hTCEpi cells, albeit at a modest level (8% of the cells). Here, we describe this novel anionic liposomal formulation intended to enhance the delivery of small cargo molecules in situ .